On Representation Theorem for Algebras with Three Commuting Involutions - Amir Mohammed; Baida Abdullah; Nadwa Younis (Al-Rafidain Journal of Computer Sciences and Mathematics)
Algebras with three commuting involutions are represented as commutants of one-generated ¯ – £ – subalgebras of algebras of vector-space endomorphisms where  ¯ – £ and are involutions of a prefixed type.